Sistem Pemantauan dan Pengendalian Kekeruhan Berbasis Internet of Things Untuk Aplikasi Pada Proses Pengolahan Air Bersih - Satriananda; Ratna Sari; Akmalul Fata; Atthariq4 (Jurnal Serambi Engineering, 2024)
Water treatment faces challenges in determining the right coagulant dosage due to the slow and manual Jar Test method. It cannot respond quickly to changing natural conditions affecting raw water quality. If turbidity increases and the coagulant dosage relies on outdated data, water quality suffers. Conversely, reduced turbidity with the same coagulant dose results in wasteful spending. To tackle this challenge, this research develops an IoT-based system solution for monitoring and controlling the system. Real-time sensors continuously monitor raw water conditions and relay data to a microcontroller. The microcontroller, in turn, adjusts the coagulant pump via a relay. This innovative system offers a solution for water treatment plants to enhance efficiency and adapt to dynamic environmental factors, ultimately improving the quality and cost-effectiveness of water treatment processes.